Selective Modernisation and Local Wisdom in Pesantren Management at Al-Luqmaniyyah Yogyakarta: A Maqasid-Informed Interpretation - Sarif Hidayatulloh; Nur Saidah; Muhammad Sabri (Sunan Kalijaga International Journal on Islamic Educational Research, 2026)
Educational globalisation challenges traditional Islamic educational institutions to modernise their management while preserving religious identity, cultural traditions, and social legitimacy. Existing studies often frame pesantren adaptation as either modernisation or preservation, offering limited insight into how both are selectively negotiated within institutional management. This qualitative case study examines how Pondok Pesantren Al-Luqmaniyyah Yogyakarta responds to educational globalisation while sustaining local wisdom, internal cohesion, and external legitimacy through the perspective of maqasid al-shariah. Data were collected from 17 purposively selected informants, including institutional leaders, administrators, ustaz, santri, alumni, and community leaders, and supplemented by observations and institutional documents. The data were analysed thematically and subsequently interpreted using a maqasid al-shariah framework. The findings reveal three interconnected patterns: selective modernisation through improved planning, organisational management, and digital administration; preservation of local wisdom through musyawarah, collective responsibility, respect for teachers, simplicity, and community service; and a maqasid-oriented managerial orientation reflected in religious learning, intellectual development, student welfare, character formation, and resource accountability. However, these practices demonstrate interpretive alignment with maqasid al-shariah rather than empirical evidence of achieved maqasid outcomes. The study proposes a contextual value-filtered management model showing how pesantren can adopt contemporary managerial practices while maintaining institutional identity, ethical commitments, and public benefit.